India and its pluralistic health system - a new philosophy for Universal Health Coverage - Sarika Chaturvedi; John Porter; Geetha Krishnan Gopalakrishna Pillai; Leena Abraham; Darshan Shankar; Bhushan Patwardhan (Elsevier, 2023)
Summary: In this article we attempt to put forth insights into using traditional medicine (TM) systems to achieve Universal Health Coverage (UHC). We discuss the need for reimagining India's health system and the importance of an inclusive approach for UHC. We comprehend the challenges with appropriate use of TM systems and the lessons from international experience of integrating TM systems. We highlight the pathways for better utilization of TM systems for UHC in India.